2004
DOI: 10.1023/b:emas.0000016793.13260.6e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Temporal Variation in Methane Emission from Different Rice Cultivars under the Influence of Weeds

Abstract: A study of temporal variation in methane efflux from the rice-fields indicated that weeds could modulate the CH4 emission by transporting atmospheric O2 more efficiently than rice plants to the rhizosphere, which suppressed CH4 formation in the oxic condition, inhibiting methanogenic activity. A more oxic environment in the sediment was reflected by the higher redox potential in the weed growing plots. Besides, cultivar differences in methane efflux might be attributed to various plant activities, more importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Factors like parential metrial, redox state, fertilization level, pesticide application, mineralogy, rice cultivar, and growth stage may also influence the geography of the microbial community and DOM [ 29 , 48 53 ]. In submerged paddy soil, rice aerenchyma enables the transport of atmospheric O 2 to the roots [ 54 ], influencing soil redox states [ 55 ]; moreover, rice straw and stubble are assumed to provide substrates for microbial activity in the early growth stage, while exudates become more important during late tillering and ripening [ 56 , 57 ]. Therefore, the effect of the rice plant on the soil microbial community largely depends on the plants growth stage.…”
Section: Discussionmentioning
confidence: 99%
“…Factors like parential metrial, redox state, fertilization level, pesticide application, mineralogy, rice cultivar, and growth stage may also influence the geography of the microbial community and DOM [ 29 , 48 53 ]. In submerged paddy soil, rice aerenchyma enables the transport of atmospheric O 2 to the roots [ 54 ], influencing soil redox states [ 55 ]; moreover, rice straw and stubble are assumed to provide substrates for microbial activity in the early growth stage, while exudates become more important during late tillering and ripening [ 56 , 57 ]. Therefore, the effect of the rice plant on the soil microbial community largely depends on the plants growth stage.…”
Section: Discussionmentioning
confidence: 99%
“…Rice that is grown in submerged paddy soils form aerenchyma which enable the transport of atmospheric O 2 to the roots (Armstrong, 1971, Begg et al, 1994, where a higher redox potential (Flessa and Fischer, 1992;Tyagi et al, 2004) mediates the detoxification of Mn 4+ , Fe 2+ by oxidation and results in the precipitation of Mn and Fe oxides in the root apoplast, which is visible as so-called plaque at the root surface (Trolldenier, 1988). The formation of these plaques can restrict the acquisition of phytotoxic elements such as Cu (Greipsson (1994), Ni (Greipsson, 1995), Cd (Lui et al, 2008) and As by rice (Bravin et al, 2008;Liu et al, 2005).…”
Section: Redox Cycling and Ph Conditionsmentioning
confidence: 99%
“…Our experimental results showed that malic, citric, and succinic acid were positively correlated with CH 4 emission fluxes (Table 3), and the SEM showed that organic acids directly and positively affected CH 4 emission fluxes (Figure 6). This may be because organic acids are easily decomposed into methanogen substrates, which promotes CH 4 production [50]. Organic acids are recognized as phytotoxins in anaerobic soils.…”
Section: Effect Of Organic Acids On Ch 4 Emissionsmentioning
confidence: 99%